Fast UWB wireless connectivity for MIMO multi-user - Mohammed, Ahmed R.; Al-Khateeb, Khalid A. Saeed; Islam, Md. Rafiqul; Khan, Sheroz; Al-Khateeb, Wajdi Fawzi Mohammed; Alam, A. H. M. Zahirul; Hameed, Shihab A. (2013)
The wired connectivity for the increasing number of peripheral devices to complement computer functions has become so large and inconvenient that wireless connectivity has become a necessity. Wireless connectivity is also necessary for digital systems in industrial, commercial, medical, military and domestic applications. A fast digital technique is proposed, based on Impulse Radio Ultra-Wide Band (IR-UWB) technology. It is theoretically analysed and practically implemented with excellent results. The suggested scheme is potentially best short range UWB wireless technology in terms of speed, capacity, power, cost and spectral mask, which complies with FCC regulations. It overcomes interference with all existing narrowband systems including GPS, PCS, WiMAX, WLAN 802.11b and 802.11a, and surpasses existing techniques, which have limited interference mitigation levels or mitigation at the cost of both reduced performance or increased system complexity. The proposed UWB pulses are portions of sine waves, which is a novel application of simple pulse shapes based on half rectified or mono cycle sine waves in the GHz range. Theoretical analysis and results obtained by simulation show excellent consistency with results obtained by experimental measurements. The technique can be used with more than one user at a time. Two users can be connected simultaneously each with 1 Gbps. The spectrum of one is centred at 4.5 GHz and the other is centered around 9 GHz. One user can operate with 2Gbps.